2017
DOI: 10.1038/s41598-017-07709-4
|View full text |Cite
|
Sign up to set email alerts
|

Direct Detection Electron Energy-Loss Spectroscopy: A Method to Push the Limits of Resolution and Sensitivity

Abstract: In many cases, electron counting with direct detection sensors offers improved resolution, lower noise, and higher pixel density compared to conventional, indirect detection sensors for electron microscopy applications. Direct detection technology has previously been utilized, with great success, for imaging and diffraction, but potential advantages for spectroscopy remain unexplored. Here we compare the performance of a direct detection sensor operated in counting mode and an indirect detection sensor (scinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(80 citation statements)
references
References 60 publications
0
80
0
Order By: Relevance
“…New hardware and techniques are being implemented to obtain real-time compositional information from materials within the LC-STEM concurrent with in-situ observation. 23,31 Nanoscale corrosion pathways, like the one identified in this work, could have a profound impact on the degradation behavior of bulk materials. This work suggests that the types of electrochemically active interfaces that typify and pervade the steel microstructure may participate in accelerated corrosion mechanisms that, extrapolated to the bulk-scale, would create percolation networks that expose the interior body of the steel to corrosive conditions much sooner than predicted by uniform corrosion models.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…New hardware and techniques are being implemented to obtain real-time compositional information from materials within the LC-STEM concurrent with in-situ observation. 23,31 Nanoscale corrosion pathways, like the one identified in this work, could have a profound impact on the degradation behavior of bulk materials. This work suggests that the types of electrochemically active interfaces that typify and pervade the steel microstructure may participate in accelerated corrosion mechanisms that, extrapolated to the bulk-scale, would create percolation networks that expose the interior body of the steel to corrosive conditions much sooner than predicted by uniform corrosion models.…”
Section: Discussionmentioning
confidence: 65%
“…Further understanding of the corrosion product deposition mechanisms could be achieved by implementing new instrumentation and methods that are complementary to in-situ TEM and that enable tracking of the iron oxide evolution in-situ. 22,31 Overlaying the initial grain boundary outline onto the postmortem image (Fig. 4a, b) revealed that the cementite grain had moved relative to its initial position (confirmed via TEM and spot diffraction analysis), rotating from its initial 25 degrees to a final 20 degrees relative to the fluid flow direction (Fig.…”
Section: Localized Progressionmentioning
confidence: 88%
“…Signal to noise ratio remains an open issue when acquiring spectra far outside the CBED disks. The current manuscript shows, that acceptable signal levels can be obtained, and progress in single electron detectors, is providing an attractive route to further improve the signal to noise ratio and open a new era of band structure studies with EELS in TEM …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, systematic efforts towards filter design based on matter waves interference into potential superlattices by manipulating the emerged resonances have been recorded 24 , with the obtained results being experimentally tested 25 . Since then, interference-based energy filters have been used to perform very accurate scanning tunneling spectroscopic measurements 26 and to execute electron counting with high resolution and sensitivity 27 . Most significantly, similar potential distributions with increased selectivity have played the role of modules in interferometric experiments complementing the field of electron holography 28 and controlling the quantum transport phenomena in nanoscale systems via time -dependent fields 29 .…”
Section: Optimally Sharp Energy Filtering Of Quantum Particles Via Homentioning
confidence: 99%